Respuesta :

[tex]\\ \sf\longmapsto f(x+4)=3x+2[/tex]

  • Taking y=x+4
  • so x=y-4

[tex]\\ \sf\longmapsto f(y)=3(y-4)+2[/tex]

[tex]\\ \sf\longmapsto f(y)=3y-12+2[/tex]

[tex]\\ \sf\longmapsto f(y)=3y-10[/tex]

Hence

[tex]\\ \sf\longmapsto f(x)=3x-10[/tex]

So

[tex]\\ \sf\longmapsto f(4)=3(4)-10[/tex]

[tex]\\ \sf\longmapsto f(4)=12-10[/tex]

[tex]\\ \sf\longmapsto f(4)=2[/tex]

caylus

Answer: 2

hi,

Step-by-step explanation:

[tex]f(x+4)=3x+2\\\\Let\ say\ y=x+4\ or\ x=y-4\\\\f(y)=3*(y-4)+2=3y-12+2=3y-10\\\\so\ f(x)=3x-10\\\\and\ f(4)=3*4-10=12-10=2\\[/tex]